Health Inequalities, Deprivation, Immigration and Aboriginality in Canada: A Geographic Perspective - Pampalon, Robert (Can J Public Health, 2010)
Objective: This study explores the contribution of deprivation, immigration and Aboriginal status to survival in various parts of Canada. It is hypothesized that differences in the magnitude of survival inequalities according to deprivation across Canada are attenuated when immigration and Aboriginal status are accounted for. Methods: The study is based on a file linking the 1991 census and a follow-up of mortality from 1991 to 2001. Geographic areas are the Canadian regions, the census metropolitan areas (CMAs) of Montréal, Toronto and Vancouver as well as the metropolitan-influenced zones. Deprivation is measured through a Canadian deprivation index. Immigration is based on declared place of birth and Aboriginal status on ethnic origin, registered treaty Indian status and Band or First Nation membership. Survival is modelized through Cox regression and two sets of models are produced for every geographic area. Results: Survival is associated with deprivation, immigration and Aboriginal status in most parts of Canada. After accounting for immigration and Aboriginal status, differences in the magnitude of survival inequalities related to deprivation across Canada are attenuated. Such inequalities are highly reduced in the Prairies and remote hinterland and slightly increased in the CMA of Toronto. Nevertheless, high survival inequalities related to deprivation remain in Canada, namely in the Prairies and, to a lesser degree, in British Columbia and the CMA of Vancouver. Conclusion: After accounting for immigration and Aboriginal status, differences in the magnitude of survival inequalities according to deprivation across Canada are attenuated but not completely eliminated.